2019
DOI: 10.2478/hjbpa-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Role of Financial Inclusion to Stability: The Case of Indonesia’s Sharia Banking

Abstract: Public access to the services of financial institutions determines the revenues amount of financial institutions. The growth of bank account helps banks to manage the financing service that provides for the community. This study examines the relationship of financial inclusion and financial stability, especially in Indonesia's Sharia banking. Financial inclusion defined as community access to financial services which peroxided by deposits, while the financial stability of Sharia banking is measured by Non Perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
3
6
0
Order By: Relevance
“…Further, respondents agreed that banks are able to keep certain amount of money that satisfy withdrawals, usage of bank accounts by customers affects bank stability, banks can create money to increase money supply in the economy and that banks earns interest rates from the borrowers depending on the category of the loan. These findings approve the research inferences by Widarwati, Sari and Nurmalasari (2019) which showed that financial inclusion proxy deposits positively affected financial stability. www.ijcab.org Results on assessing on service delivery revealed that there is improved utilization of resources with commercial banks listed in NSE thus resulting in effective cost-cutting, customers have access to all relevant information on financial services and products to permit them make informed decisions on usage, there is ease and comfort of accessing and using financial services and that there is improved delivery of service by commercial banks listed in NSE thus leading to enhanced customer satisfaction.…”
Section: Discussion Of Study Findingssupporting
confidence: 91%
See 3 more Smart Citations
“…Further, respondents agreed that banks are able to keep certain amount of money that satisfy withdrawals, usage of bank accounts by customers affects bank stability, banks can create money to increase money supply in the economy and that banks earns interest rates from the borrowers depending on the category of the loan. These findings approve the research inferences by Widarwati, Sari and Nurmalasari (2019) which showed that financial inclusion proxy deposits positively affected financial stability. www.ijcab.org Results on assessing on service delivery revealed that there is improved utilization of resources with commercial banks listed in NSE thus resulting in effective cost-cutting, customers have access to all relevant information on financial services and products to permit them make informed decisions on usage, there is ease and comfort of accessing and using financial services and that there is improved delivery of service by commercial banks listed in NSE thus leading to enhanced customer satisfaction.…”
Section: Discussion Of Study Findingssupporting
confidence: 91%
“…Further, majority of participants felt that banks are able to keep certain amount of money that satisfy withdrawals, usage of bank accounts by customers affects bank stability, banks can create money to increase the money supply in the economy and that banks earns interest rates from the borrowers depending on the category of the loan. These findings are in accord with the study findings by Widarwati, Sari and Nurmalasari (2019) which showed that financial inclusion positively affected financial stability.…”
Section: Source: Research Data (2020)supporting
confidence: 92%
See 2 more Smart Citations
“…From an international viewpoint, this action is anticipated to maintain additional comprehensive and sustainable economic development, and can help the people wellbeing. Furthermore, financial inclusion is anticipated to sustain the financial strength as basis of firm economic progress (Widarwati, Sari & Nurmalasari, 2019). Kigsley (2013) has tinted the function of financial inclusion in tackling concerns such as worldwide poverty, income discrimination, under progress and wellbeing.…”
Section: Literature Reviewmentioning
confidence: 99%